Investigation on the Baumgarte stabilization method for dynamic analysis of constrained multibody systems - Flores, Paulo (2009)
This paper presents an investigation on the Baumgarte stabilization method for dynamic analysis of constrained multibody systems. The purpose of this work is to study the influence of the main variables that affect the constraints violation, namely, the values of the Baumgarte parameters. In the process, the formulation of the dynamic equations of motion of constrained multibody systems and the main issues of the Baumgarte stabilization method are revised. Attention is given to the techniques to help in the Baumgarte parameters selection. A demonstrative example is presented and the results of some simulations are discussed.